Konsep Penebusan Dosa dalam Bilangan 21:4-9 dalam Wujud Budaya Famatö Harimao bagi Masyarakat Nias - Icha Debora Gulo; Firman Panjaitan (Sekolah Tinggi Theologia Nazarene Indonesia, 2022)
The concept and teachings of redemption become a major desire for every religious person, including Christians. Through the teaching of atonement, every people are made aware that God works to liberate sinful humans through His acts of love. This work of God's liberation is understood as a form of human release from the power of sin so this teaching about redemption becomes the basic core of every religious teaching. One of the redeeming teachings of the Bible is found in the narrative of the bronze serpent statue in Numbers 21:4-9. However, it is not the only religion that talks about the teachings of redemption, every culture also has the teachings of redemption, including in this case the culture in the Nias community called Famatö Harimao. By using qualitative methods, especially library research and textual interpretation approaches, this research shows that the narrative of the copper snake statue can be used as the basis for contextualizing Famatö Harimao culture. The results of the study show that the Famatö Harimao culture which has been contextualized through the basis of Numbers 21:4-9 can still be lived and lived by the people of Nias because through this culture the people of Nias have a concept of redemption that is culturally and biblically accountable.